Grape pomace polyphenols improve insulin response to a standard meal in healthy individuals: A pilot study. Issue 6 (December 2019) - Costabile, G.; Vitale, M.; Luongo, D.; Naviglio, D.; Vetrani, C.; Ciciola, P.; Tura, A.; Castello, F.; Mena, P.; Del Rio, D.; Capaldo, B.; Rivellese, A.A.; et al.
S U M M A R Y: Background & aims: Dietary polyphenols have beneficial effects on glucose/lipid metabolism in subjects at high risk to develop type 2 diabetes; however, the underlying mechanisms are not clear. We aimed to evaluate: 1) the acute effects of the consumption of a drink rich in polyphenols from red grape pomace (RGPD) on glucose/insulin and triglyceride responses to a standard meal in healthy individuals, and, 2) the relationship between plasma levels of phenolic metabolites and metabolic parameters. Methods: Twelve healthy men, aged 20–40 years participated in a randomized, controlled study according to a cross-over design. After a 3-day low–polyphenol diet, all participants consumed, on two different days and separated by a one week interval, after an overnight fast, a drink rich in polyphenols (1.562 g gallic acid equivalents (GAE)) or a control drink (CD, no polyphenols), followed after 3 h by a standard meal (960 kcal, 18% protein, 30% fat, 52% CHO). Blood samples were taken at fasting, 3 h after the drink, over 5 h after the standard meal and at fasting on the next day to measure plasma concentrations of glucose, insulin, triglyceride and phenolic metabolites. Results: Glycemic and triglyceride post-meal responses were similar after both the RGPD and the control drink. In contrast, postprandial insulin incremental area (iAUC0–5h ) was 31% lower (p < 0.05), insulin secretion index was 18% lower (p < 0.016) and insulin sensitivity (SI ) index was 36% higher (p = 0.037) after the RGPD compared to CD. Among phenolic metabolites, gallic acid correlated inversely with the insulin response (r = −0.604; p = 0.032) and positively with the SI index (r = 0.588, p = 0.037). Conclusions: RGPD consumption acutely reduced postprandial insulin levels and improved insulin sensitivity. This effect could be likely related to the increase in gallic acid levels. This drink, added to usual diet, could contribute to increase the daily intake of polyphenols, with potential health benefits. Clinicaltrials.gov identifier: NCT02865278.